ANALISIS PERLINDUNGAN HUKUM BAGI KREDITUR ATAS PENETAPAN EKSEKUSI PERJANJIAN KREDIT DENGAN JAMINAN HAK TANGGUNGAN PADA PT.BANK RAKYAT INDONESIA - Marissa Illahi Putri; Mardalena Hanifah; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Credit position in the business world should receive legal protection from astrong guarantee institution and can provide legal certainty for all interestedparties regulated in a special regulation on it. The process of providing credit withcollateral often occurs that the creditor is harmed when the debtor defaults. In fact,creditors holding Dependent Rights have the right to sell the guarantee on theirown power if the debtor defaults as stipulated in Article 6 of Law No. 4 of 1996.However, in practice there is often resistance on the part of the executed debtor,thus hindering the execution of the Right of Dependent.The purpose of the studyis first, legal protection for creditors for the determination of credit agreementexecution. Second, the guarantee of the rights of dependents and the interpretationof execution based on the provisions of the Law on Rights of DependentsThis type of research can be classified into normative types of research. Byfocusing on the scope of legal principles. This research uses data sources in theform of basic norms, basic regulations and laws and regulations from primary dataand archives of execution case files from secondary data, and data collectiontechniques are carried out by library reasearch.From the results of the study, it can be concluded that the creditor's legalprotection for the determination of the execution of credit agreements withcollateral is that the Certificate of Liability has an Executive Title as stipulated inArticle 14 paragraph (2) of Law No. 4 of 1996, so that creditors have full power toexecute the guarantee and get full debt repayment if the debtor defaults. Theinterpretation of the provisions of the article in Law Number 4 of 1996 is to givethe right to sell the object of the Dependent Rights on their own power (parateexecutie) through auction without asking for assistance from the Court, and eventhough the object of the Dependent Rights has moved into the property of otherparties, creditors can still exercise their rights to exercise their rights If the debtordefaults.Keywords: Creditor - Debitor - Legal protection